Factors that Influence Low Mother Visits to Posyandu During the Covid-19 Pandemic in Nagasaribu Village V Districts Lintongnihuta Districts Humbang Hasundutan Year 2022 - Fetti Lusianna Simanjuntak; Astaria Br Ginting; Desi Asmarani; Siti Patimah Br Ginting; Ade Rachmat Yudiyanto (Institute of Computer Science (IOCS), 2022)
Integrated service post is an activity organized for the benefit of the community so that its establishment, implementation and utilization requires active participation from the community. The community can take an active role in the form of monthly participation in weighing children under five so that it can improve the nutritional status of toddlers. This research aims to know the factors that influence the low visits of mothers of children under five to the integrated service post during the COVID-19 pandemic in Desa Nagasaribu V Kec. Lintongnihuta Kab. Humbang Hasundutan Tahun 2022 This study is an analytical study with a cross sectional study design. The population in this study were all mothers of children under five who were in Desa Nagasaribu V Kec. Lintongnihuta Kab. Humbang Hasundutan Tahun 2022 as many as 117 people. Samples were obtained as many as 54 people. Sampling technique with random sampling. Analysis of research data consisted of univariate and bivariate analysis with Chi Square test. The results showed that there was a relationship between knowledge and visits by mothers of children under five to the integrated service post during the COVID-19 pandemic (p = 0.019). There is a relationship between attitude and visits to integrated service post during the COVID-19 pandemic (p = 0.000). There was no relationship between age and mother's visit to integrated service post during the COVID-19 pandemic (p = 0.053). There is a relationship between education and the visit of mothers of children under five to the integrated service post during the COVID-19 pandemic (p = 0.045). There is a relationship between work and the visit of mothers of children under five to the integrated service post during the COVID-19 pandemic (p = 0.001). Cadres are expected to always provide knowledge, understanding and health education about the importance of integrated service post and the benefits of integrated service post for toddlers so that mothers of toddlers are motivated to visit integrated service post and show a caring attitude about integrated service post implementation and activities.